Pengaruh Pemberian Pupuk Kandang Terhadap Pertumbuhan Bayam Konsumsi (Amaranthus sp.) - Susanti, Ambar; Aisyah, Siti Nur; Masruri, Afiq (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study was to determine the effect of manure application on the growth of consumption spinach (Amaranthus sp). The research was conducted at the Faculty of Agriculture, University of KH.A. Wahab Hasbullah in December 2022 to March 2023. The manure used in this study included cow manure, goat manure and chicken manure. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were PK0 (control without adding fertilizer), PK1 (adding cow manure), PK2 (adding goat manure), and PK3 (adding chicken manure). The research data were analyzed using the F test at the 5% level and continued with the BNT test at the 5% level. The results showed that the addition of manure from the waste raw materials of the three types of manure affected plant height, number and leaf area of consumption spinach plants better than the control. Manure as raw material for goat manure had significant plant height (21.25 cm), number of leaves (8.33), and leaf area (3.72 cm2) compared to the other 3 treatments. Keywords: manure, growth, consumption of spinach